How to Diagnose, Treat, and Monitor Treatment Response in Patients with Multiple Myeloma - Wulyo Rajabto; Dimas Priantono (Acta Medica Indonesiana, 2022)
Multiple myeloma (MM) is a B-cell malignancy characterized by clonal proliferation of malignant plasma cells in the bone marrow, monoclonal protein production in the serum, and organ dysfunction. It is part of a disease spectrum called plasma cell disorders, and to establish the diagnosis, a bone marrow biopsy should be conducted with clinical signs of end-organ damage and/or significantly elevated monoclonal protein (M-protein). MM can also be diagnosed without end-organ damage when certain conditions are met since the International Myeloma Working Group (IMWG) has come up with new diagnostic criteria for multiple myeloma. Treatment for all patients with MM aims to enhance the depth and duration of response while limiting drug toxicity to lengthen survival, improve quality of life, alleviate symptoms and prevent further organ damage. Development of new drugs has improved the survival of patients4 Available tests for monitoring of patients with MM most often include assessments of monoclonal paraprotein and serum-free light chain levels with bone marrow examination, which directly identifies the level of malignant plasma cells.